Data protection and the cloud - are you really managing the risks?. - TICHER, PAUL (IT GOVERNANCE LTD, 2018)
With a view to helping managers ask the right questions, Data Protection and the Cloud explains how you can effectively manage the risks associated with the Cloud and meet regulatory requirements.
Keywords: Data protection.; Computer security.; Computer Security; Protection de l'information (Informatique); Sécurité informatique.; Computer security; Data protection